On the primitive and derivative characters of the families of beetles (Coleoptera). - Abdullah, Mohammad (Contributions to Entomology = Beiträge zur Entomologie, 1971)
Phylogenetic conclusions on the primitive or derivative alternative of the distinguishing morphological and other characters of the families and other groups of the Coleoptera are given.